The Role of Meaningfulness and Environmental Awareness in Fostering Happiness and Revisit Intention in Biophilic Cafés - Anang Hermansyah; Hera Rachmahani; Nuri Herachwati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Biophilic design integrates natural elements into built environments to enhance well-being. While its benefits for satisfaction and stress reduction are well-documented, limited research explores how biophilic café environments evoke psychological and emotional responses that influence visitor behaviour. This study examines how meaningfulness and environmental awareness in biophilic cafés foster happiness and shape revisit intention. Drawing on Attention Restoration Theory and Place Attachment Theory, the study conceptualizes these pathways as symbolic and emotional mechanisms through which design influences experience and behaviour. A survey was conducted through Prolific, targeting 219 respondents in the United Kingdom who had previously visited cafés with visible biophilic design features. Data were analysed using structural equation modelling to test the hypothesized relationships between meaningfulness, environmental awareness, happiness, and revisit intention. The findings reveal that meaningful and environmental awareness self enhance happiness, which in turn increases revisit intention. Theoretically, this research extends biophilic design literature by uncovering the psychological pathways linking symbolic and emotional experiences to behavioural outcomes in hospitality contexts. Practically, it offers insights for hospitality managers and designers to create emotionally impactful, meaningful spaces that evoke well-being and loyalty suggesting that designing for connection and meaning is as essential as delivering comfort or service quality.